Adsorption of arsenic on granular ferric hydroxide (GEH®). Impact of initial concentration of arsenic(V) on kinetics and equilibrium state - Saldaña-Robles, Adriana; Saldaña-Robles, Alberto; Márquez-Herrera, Alfredo; de la Luz Ruiz-Aguilar, Graciela Ma; Saldaña-Robles, Noé (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
The present study discusses the adsorption kinetics of arsenic(V) on granular ferric hydroxide (GEH) and the GEH adsorption capacity for arsenic(V) at equilibrium. The impact of temperature on GEH adsorption capacity was studied, as well as the effects of the initial concentration of arsenic(V) and GEH concentration on the adsorption rates of arsenic(V). The Freundlich isotherm describes the arsenic(V) adsorption behavior reasonably well (r2 > 0.965). The adsorption kinetics was studied by fitting the experimental data to both first-order and second-order models. The maximum adsorption capacity of arsenic(V) on GEH was 2.701 mg·g–1, which is higher than the adsorption capacities of other adsorbents reported. The kinetics of arsenic(V) adsorption was well defined by the second-order model, with the correlation coefficients in the range of 0.960–0.987. This study shows that due to its properties, GEH is a good candidate for removal of arsenic(V) from groundwater.
Environment Protection Engineering. Vol. 44, 2018, nr 3, s. 51-62
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma